2010
DOI: 10.1002/adem.200980019
|View full text |Cite
|
Sign up to set email alerts
|

Annealing of Biodegradable Polymer Induced by Femtosecond Laser Micromachining

Abstract: Femtosecond laser is a potential tool for net shape processing of biodegradable polymers. However, laser processing of polymeric material is still a challenge and the effects induced by laser ablation needs to be investigated. Poly(ε‐caprolactone) was micromachined at high fluence and the heat affected zone was characterized. Two different phases of microstructure, namely the annealed spherulite zone and the amorphous zone, are found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Recently, laser applications have grown significantly in plastic industries because it is now possible to achieve production with a superior quality finishing along with greater process reliability. The major advantages of laser processing are that the process is non‐contact and non‐contaminant, flexible, easy to control, and highly reproducible …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, laser applications have grown significantly in plastic industries because it is now possible to achieve production with a superior quality finishing along with greater process reliability. The major advantages of laser processing are that the process is non‐contact and non‐contaminant, flexible, easy to control, and highly reproducible …”
Section: Introductionmentioning
confidence: 99%
“…The major advantages of laser processing are that the process is non-contact and non-contaminant, flexible, easy to control, and highly reproducible. 13,[17][18][19] The process of microhole formation is occurring based on the laser-material interaction. It should be noted that there are 2 main mechanisms for the laser-materials interaction: One is the photo-thermal process and the other is the photo-chemical process.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that HAZ increases with the laser power and decreases with the cutting velocity. Yeong et al [50] analyzed the effect of femtosecond laser micromachining on poly-E-caprolactone (PCL). Ortiz et al [51] examined the picosecond laser ablation of PLLA as a function of laser fluence and degree of crystallinity.…”
Section: Laser Cuttingmentioning
confidence: 99%